2018
DOI: 10.5194/acp-18-4297-2018
|View full text |Cite
|
Sign up to set email alerts
|

Using eddy covariance to measure the dependence of air–sea CO<sub>2</sub> exchange rate on friction velocity

Abstract: Abstract. Parameterisation of the air-sea gas transfer velocity of CO 2 and other trace gases under open-ocean conditions has been a focus of air-sea interaction research and is required for accurately determining ocean carbon uptake. Ships are the most widely used platform for air-sea flux measurements but the quality of the data can be compromised by airflow distortion and sensor cross-sensitivity effects. Recent improvements in the understanding of these effects have led to enhanced corrections to the shipb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…The SOAP study was carried out on the RV Tangaroa during February and March 2012 in the biologically productive frontal waters of the Chatham Rise (44 • S, 174-181 • E), east of New Zealand, where nutrient-rich sub-Antarctic water meets warmer subtropical water (Law et al, 2017). The voyage strategy was to survey regional surface biogeochemical distributions during the night and focus sampling during the day on the areas showing highest DMS concentrations, chlorophyll a and CO 2 drawdown.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOAP study was carried out on the RV Tangaroa during February and March 2012 in the biologically productive frontal waters of the Chatham Rise (44 • S, 174-181 • E), east of New Zealand, where nutrient-rich sub-Antarctic water meets warmer subtropical water (Law et al, 2017). The voyage strategy was to survey regional surface biogeochemical distributions during the night and focus sampling during the day on the areas showing highest DMS concentrations, chlorophyll a and CO 2 drawdown.…”
Section: Methodsmentioning
confidence: 99%
“…The SOAP experiment (Law et al, 2017) examined the role of surface ocean biogeochemistry in influencing marine boundary layer aerosol, with a strategy of targeting phytoplankton blooms east of New Zealand, which were potentially significant source regions for aerosol precursors. These blooms represented a significant source of DMS (Bell et al, 2015) and provided a valuable opportunity for validation of micrometeorological techniques and parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…(2): the bulk flux (corrected for airflow distortion) from the nearby RV Tangaroa, or the directly measured, motion-corrected u * from EC measurements on board Tangaroa. The gradient fluxes estimated using the EC u * (Landwehr et al, 2018) are shown in Fig. 5a in red, overlain on the EC continuous 10 min data, for 20 days of the SOAP voyage.…”
Section: Gradient Fluxesmentioning
confidence: 99%
“…This slope is very close to that from a direct regression between u * from bulk fluxes and u * from EC. This suggests that the CFD modelling has overcompensated for the airflow acceleration, resulting in a u * that is too low, as examined in detail by Landwehr et al (2018). It is likely that small-scale features of the Tangaroa -such as the foremast and railings, which were not included in the modelmay have a significant effect on the airflow-corrected wind speeds.…”
Section: Gradient Fluxesmentioning
confidence: 99%
See 1 more Smart Citation